Towards the prosody of persuasion in competitive negotiation. The relationship between f0 and negotiation success in same sex sales tasks - Michalsky, Jan; Schoormann, Heike; Schultze, Thomas (Proceedings of the Annual Conference of the International Speech Communication Association, INTERSPEECH, 2019)
Prosodic features play a key role in a speaker's persuasive power. However, previous studies on persuasion have been focused on public speaking and the signaling of leadership, while acoustic studies on negotiation have been primarily concerned with cooperative interactions. In this study we are taking a first step into investigating the role of acoustic-prosodic cues in competitive negotiation, focusing on f0 in same-sex negotiations. Specifically, we ask whether the prosodic correlates of persuasive speech are comparable for public speaking and negotiation. Sixty-two speakers (44f/18m) in 31 same-sex pairs participated in a competitive task to bargain over the selling price of a fictional company. We find a significant correlation between a speaker's f0 features and his/her interlocutor's concession range. In line with findings from public speaking, greater f0 excursions and higher f0 minima correlate with negotiation success. However, while the female speakers also show an expected elevated f0 mean, the opposite is the case for male speakers. We propose that in competitive negotiation, displaying dominance may overrule showing passion in contrast to public speaking, but only for male speakers.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Charisma; Competitive negotiation; F0; Persuasion; Prosody; Sociophonetics; Voice profiling